Gross ecosystem product accounting in Miyun County: the supply and use of ecosystem services - Yu-qian Shen; Yu-qian Shen; Xiao Yi; Meng Chen; Meng Chen; Zhi-yun Ouyang (Frontiers in Ecology and Evolution, 2024)
The ability of an ecosystem to provide services differs from its actual consumption and use by human society. Overuse of ecosystems can degrade ecosystems. In order to evaluate the supply capacity and use status of the ecosystem in Miyun County, so as to better apply the ecosystem services to different policies and management, the supply and use of 10 types of ecosystem services in Miyun County were calculated by using value indicators, namely potential gross ecosystem product (GEP) and actual gross ecosystem product. The results show that: (1) In 2020, potential gross ecosystem product of Miyun County is 254.32 billion yuan, and actual gross ecosystem product is 53.28 billion yuan, accounting for 21% of the potential gross ecosystem product. (2) Among all kinds of ecosystem services, the contribution of water conservation services in potential gross ecosystem product is the highest, and the contribution of climate regulation services in actual gross ecosystem product is the highest. (3) The contribution of wetland was the highest in potential gross ecosystem product, while the contribution of forest was the highest in actual gross ecosystem product. (4) Natural ecosystem area and vegetation coverage are the main factors affecting potential gross ecosystem product, while actual gross ecosystem product is mainly affected by GDP and population. (5) By studying the potential supply and actual use of ecosystem services, we evaluated and distinguished between the services that ecosystem could produce and the services that were actually used by humans, and compared the supply capacity and actual use to assess the sustainability of ecosystem services, in order to formulate different policies and management measures for gross ecosystem product surplus and deficit regions. Potential gross ecosystem product could provide data support for the assessment of ecological protection benefits. Actual gross ecosystem product could be included in the system of national accounts, and as a standard for ecological compensation and ecological trading. Confusing potential supply and actual use in policy application would affect the effect of policy implementation, and distinguishing them could ensure policy implementation. The relative size of the relationship between the two could reflect the present and future levels of human well-being in a region. Both together provided management basis and policy-making support for guiding regional ecological protection and sustainable development.